2015
DOI: 10.1159/000442155
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hypoglycemia in Children after Gastric Surgery: Clinical Characterization and Pathophysiology

Abstract: Background/Aims: Dumping syndrome is a common complication in children after fundoplication and other gastric surgeries and is characterized by postprandial hypoglycemia (PPH). Children with PPH have an exaggerated GLP-1 response to a meal with an exaggerated insulin surge and subsequent hypoglycemia. We evaluated the role of GLP-1 in the pathogenesis of PPH by examining the effects of GLP-1 receptor blockade on glucose and insulin response to a meal. Methods: Six children with known PPH after surgery underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…The pathogenesis is likely related to the early development of hyperinsulinaemic (reactive) hypoglycaemia [1]. Calabria et al [2] demonstrated that the exaggerated insulin response to a meal, seen in children with post-prandial hypoglycaemia after gastric surgery, is at least in part due to the effects of GLP-1 on the pancreatic β-cell, as the blockade of the GLP-1 receptor with exendin (9–39) blunted the insulin response even in the presence of hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pathogenesis is likely related to the early development of hyperinsulinaemic (reactive) hypoglycaemia [1]. Calabria et al [2] demonstrated that the exaggerated insulin response to a meal, seen in children with post-prandial hypoglycaemia after gastric surgery, is at least in part due to the effects of GLP-1 on the pancreatic β-cell, as the blockade of the GLP-1 receptor with exendin (9–39) blunted the insulin response even in the presence of hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Montgomery et al [8] showed a delayed gastric emptying in patients who have repaired oesophageal atresia. Meanwhile, the role of GLP-1 that was proved to play a key role in PPHH in children after gastric surgery [2] needs to be investigated in children with PPHH following oesophageal atresia repair. Children with PPHH can present either acutely, with life-threatening symptoms such as hypoglycaemic seizures, or they could be asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gastric fundoplication wraps around a main branch of the vagus nerve; whether gastric motility worsens post-surgery due to vagal nerve injury is unknown but plausible [24]. Other potential side effects of fundoplication include dumping syndrome, worsening of esophageal motility, and the “gas-bloat syndrome” [69, 70]. There are data to suggest that the presence of a fundoplication may increase the risk of gastrointestinal bleeding [71].…”
Section: Recommendations For the Management Of Respiratory Disorders mentioning
confidence: 99%